2017
DOI: 10.3847/1538-4357/aa643c
|View full text |Cite
|
Sign up to set email alerts
|

Project 1640 Observations of Brown Dwarf GJ 758 B: Near-infrared Spectrum and Atmospheric Modeling

Abstract: The nearby Sun-like star GJ 758 hosts a cold substellar companion, GJ 758 B, at a projected separation of 30 au, previously detected in high-contrast multi-band photometric observations. In order to better constrain the companion's physical characteristics, we acquired the first low-resolution (R ∼ 50) near-infrared spectrum of it using the high-contrast hyperspectral imaging instrument Project 1640 on Palomar Observatory's 5 m Hale telescope. We obtained simultaneous images in 32 wavelength channels covering… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 53 publications
3
8
0
Order By: Relevance
“…this is in good agreement with the inferred effective temperatures of 600-750 K for Gl 758 B from multi-band imaging and spectroscopy (Vigan et al 2016;Nilsson et al 2017). Based on this consistency and the fact that the companion's orbital period must be much longer than the time baseline of the RV observations (?20 years), we conclude that Gl 758 B is likely the source of the acceleration.…”
Section: Is the Acceleration Caused By Gl 758 B?supporting
confidence: 82%
See 2 more Smart Citations
“…this is in good agreement with the inferred effective temperatures of 600-750 K for Gl 758 B from multi-band imaging and spectroscopy (Vigan et al 2016;Nilsson et al 2017). Based on this consistency and the fact that the companion's orbital period must be much longer than the time baseline of the RV observations (?20 years), we conclude that Gl 758 B is likely the source of the acceleration.…”
Section: Is the Acceleration Caused By Gl 758 B?supporting
confidence: 82%
“…Although Gl 758 B has only completed a small fraction of its orbit, the most likely orbital solutions relying solely on astrometry suggest it is eccentric with a semimajor axis between about 20 and 60 au. Nilsson et al (2017) propose that the acceleration induced by Gl 758 B should be measurable on the host star, but no evidence of a trend was observed by Vigan et al (2016) using RVs from the ELODIE spectrograph and Lick Observatory, most likely due to the relatively large uncertainties of these data sets.…”
Section: Overview Of the Gl 758 Systemmentioning
confidence: 88%
See 1 more Smart Citation
“…Depending on the adopted age of the system, evolutionary models predict masses for the com-Article number, page 1 of 5 arXiv:1806.07899v1 [astro-ph.SR] 20 Jun 2018 A&A proofs: manuscript no. 33309corr panion of between 10 and 40 M Jup (Janson et al 2011;Nilsson et al 2017;Bowler et al 2018). However, evolutionary models are highly uncertain at these low masses.…”
Section: Introductionmentioning
confidence: 98%
“…GJ 758b is a T dwarf companion separated by 30 AU from a Solar type star with an age of 5-9 Gyr (Thalmann et al 2009;Janson et al 2011). This object has been characterized before, however, previous work has demonstrated that its photometry is difficult to fit with at-mospheric models or spectra of analog objects (Vigan et al 2016;Nilsson et al 2017).…”
Section: Introductionmentioning
confidence: 99%